Enhancing Knowledge and Practical Competency in Adverse Drug Reaction Reporting Among Postgraduate Residents: A Pre-Post Interventional Study - Shoebul Haque; Fatima Khan; Afroz Abidi, (International Journal of Pharmacy Research & Technology (IJPRT), 2026)
Background: Adverse drug reaction (ADR) reporting is an important component of pharmacovigilance and patient safety. However, underreporting remains a significant challenge, often due to inadequate knowledge and training among healthcare professssionals. Educational interventions have been shown to improve awareness and reporting practices. Objective: To evaluate the effectiveness of a structured educational intervention on knowledge and practical skills related to ADR reporting among postgraduate (PG) medical students. Methods: A prospective interventional study was conducted among 70 first-year postgraduate students from various clinical and paraclinical departments. Participants underwent a pre-test assessment consisting of a structured 50-item multiple-choice questionnaire (MCQs) and ADR form-filling evaluation. A post-test was conducted using the same assessment tools. Data were analyzed using descriptive statistics, and the Wilcoxon signed-rank test was applied to compare pre and post-intervention scores. Effect size (r) and difficulty index (P) for MCQs were also calculated. Results: The mean score increased from 23.5 in the pre-test to 32.5 in the post-test, with an average improvement of 8-10 marks. A significant improvement in overall performance was observed, with 96% of students showing score enhancement. The Wilcoxon signed-rank test demonstrated a statistically significant difference (p < 0.001), with a large effect size (r = 0.79). MCQ analysis revealed a shift from predominantly difficult and moderate questions in the pre-test to mostly easy questions in the post-test. Practical skills in ADR form filling also improved substantially. Conclusion: The educational intervention significantly improved both knowledge and practical competencies related to ADR reporting among postgraduate students. Regular training programs and integration of pharmacovigilance education into postgraduate curricula are recommended to enhance ADR reporting practices and improve patient safety.